(untitled) (Biocenosis, 2012)
Tirimbina Biological Reserve (TBR) has an Environmental Education Program for over 10 years. Each year they work with a different theme, during 2010 it was “Bats”. The work dynamics consists of two stages: during the first, children of second cycle of nine schools visit Tirimbina. In the second stage, the staff of the Environmental Education Program of the Reserve visits the nine schools. The results presented below are the product of the use of questionnaires and interpretation of drawings made by children.